PENGARUH KETERLIBATAN KARYAWAN DAN KESEIMBANGAN KEHIDUPAN KERJA TERHADAP TURNOVER INTENTION - Rahayu Mardikaningsih; Samsul Arifin (Jurnal Baruna Horizon, 2022)
Business competition in the global market poses problems for companies. The problem faced by the company is not only how to set a marketing strategy for profit. Companies are faced with problems regarding the level of turnover intention of their employees. The company will spend more to train the new employee's ability if there is a turnover of its employees. So that the problem of turnover intention becomes the focus of management in order to suppress the desire of employees to quit or change jobs. This study was conducted to determine the level of turnover intention seen from employee involvement and work-life balance. This research was conducted at a company in Kediri, East Java. The research sample obtained as many as 100 respondents. The research data will be processed with SPSS using multiple linear regression analysis techniques. Based on the results of the tests that have been carried out, it is proven that employee involvement has a significant influence on the formation of turnover intention. In addition, turnover intention is also significantly influenced by work-life balance. Work involvement and work-life balance together have a significant influence on changes in turnover intention.